Cubic Dual Ideals in BCK-Algebras - Satyanarayana, B; Agboola, A.A.A; Madhavi, U Bindu (International Journal of Mathematical Research, 2016)
In this paper we introduce the concept of cubic set to dual sub algebras and dual ideals in BCK-algebras and investigate some of its properties. The relationship between dual sub algebras and cubic dual sub algebras are given.